Planned versus Unplanned Delivery for Placenta Accreta Spectrum - Fishel Bartal, Michal; Papanna, Ramesha; Zacharias, Nikolaos M.; Soriano-Calderon, Neomary; Limas, Maria; Blackwell, Sean C.; Chen, Han-Yang; Chauhan, Suneet P.; Sibai, Baha M. (American Journal of Perinatology, 2020)
Objective Women with placenta accreta spectrum (PAS) having an unplanned delivery may have worse outcome compared with women with a planned delivery. The primary objective of this study was to compare severe maternal morbidity among women with PAS who had a planned scheduled delivery versus an unplanned delivery. Secondary objective was to compare neonatal outcomes.Study Design Retrospective cohort study at two tertiary centers (January 2009 to June 2019) of all women who underwent a hysterectomy with a histologic proven PAS. Primary outcome was severe maternal morbidity which defined as any of the following: transfusion of ≥4 RBC units or ureter/bowel injury. Neonatal outcome was a composite neonatal morbidity defined as any of the following: Apgar score's < 5 at 5 minutes, mechanical ventilation, or respiratory distress syndrome. Maternal demographic, clinical, and sonographic characteristics were compared between the two groups (planned vs. unplanned). Descriptive statistics were used as appropriate, and a statistical significance was established if p-value was < 0.05.Results Of 109 women who underwent cesarean hysterectomy for PAS, 41 (37.6%) had an unplanned delivery. There was no significant difference in the number of previous cesarean deliveries or ultrasound findings between the two groups. Women with an unplanned delivery were more likely to bleed during pregnancy than those that had a planned delivery (p = 0.04). Women with unplanned delivery had lower gestational age at delivery (30.3 vs. 33.8 weeks, p = 0.001) had a 75% higher rate of the primary outcome (63 vs. 36%, p = 0.007) and had a higher rate of intensive care unit admissions (39 vs. 17.7%, p = 0.01) compared with women with a planned delivery. The neonatal morbidity did not differ between the two groups.Conclusion Since unplanned cesarean hysterectomy among women with PAS occurs in 40% and is associated with significantly higher morbidity, interventions are needed to mitigate the rate of adverse outcomes.Key Points
Keywords: placenta accreta spectrum; morbidly adherent placenta; cesarean hysterectomy